Timeless memories : a celebration of life and humanity : conversation between Wole Soyinka and Ulli Beier - Adebowale, Oludamola (Wildeye Creative Solutions LTD, 2021)
Refer to the document
Timeless memories : elastic effects
Book
Keywords: Literature; Black authors; Wole Soyinka; Ulli Beier; Indigenous knowledge systems; Yoruba culture; Artistic collaboration; Work -- Literary collections; English literature Black authors